Place and preference effects on the association between mental health and internal migration within Great Britain. (July 2018) - Wilding, Sam; Martin, David; Moon, Graham
Abstract: Individuals with mental health needs are more likely to migrate than the general population, but the effects of migration preference and place of residence are often overlooked. These issues are addressed through the application of a novel origin and destination multilevel model to survey data. In comparison to those with good mental health, individuals with poor mental health are more likely to make undesired moves and this is moderated, but not explained by place of residence. Implications for understanding the mental health and migration relationship, and its impact on service provision are then proposed. Highlights: Mental health needs are consistently associated with internal migration. Past research overlooks the importance of migration preference for this association. Mental health is associated with moving only among those who prefer not to migrate. This finding is independent of where individuals live. This displacement may have role in explaining geographies of mental health.